Improving Economic Efficiency Through Waste Recycling And Modernizing Waste Bank Management - Mohamad Nur Utomo; Sulistya Rini Pratiwi; Farid Helmi Setyawan (International Journal Of Community Service, 2024)
Efficient waste bank management is essential for handling the growing waste volumes in landfills. Waste banks play a crucial role in local and national waste management. This program aims to boost the capacity and productivity of waste bank institutions by supporting the development of human resources in waste recycling management and implementing digital management systems. Program results demonstrate that KSM Bais, Tarakan, our partner waste bank institution, has improved its knowledge and skills in waste bank management. They have expanded their range of recyclable products, including marketable items like plastic flower jewelry, trash bins, stationery organizers, ecobricks, and other aesthetic products. Furthermore, they have created and implemented a website-based waste bank application system to streamline administrative tasks. Additionally, partners have enhanced waste bank marketing performance through website-based and online social media channels.